y/-65=-6

Simple and best practice solution for y/-65=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y/-65=-6 equation:


y in (-oo:+oo)

y/(-65) = -6 // + 6

y/(-65)+6 = 0

6-1/65*y = 0 // - 6

-1/65*y = -6 // : -1/65

y = -6/(-1/65)

y = 390

y = 390

See similar equations:

| 6/1.75=32/x | | 3x-2(3x+4)=10 | | n+3n=360 | | 90=.7x | | x/0.5=4/11 | | 6/2.875=32/x | | 55=4x+2x+1 | | 15x/3x^3 | | -2x+3=-5x | | 3/2.875=16/x | | -6(x-5)-8=2(x+3) | | 49+.07x=44+.11x | | 3/1.75=16/x | | 16(6c-1)-4=84c+16 | | lnx=0.12 | | 5p/1-18=-43 | | x+v(squared)=w(squared) | | 2/3=x/33 | | 20=-d+18 | | -2x+1+7x=31 | | -3/7a=-21 | | [2p-(5t+q)+(-9p-3t)+(8q+6t)+t-3p-5q]= | | (x-3)/10=7/2 | | -1/4×=9 | | 36+59=(20x+10)/2 | | 30+0.80r=2.30r | | c=60-0.05d | | 36+59=(20#+10)/2 | | -2x-9=-31 | | 30d+0.80r=2.30r | | 9x/2-5=13 | | (2a+4b)+(-6b-a)+(-b+7a)= |

Equations solver categories